The triumph of an accursed lineage - Arias Guillén, Fernando (Routledge, Taylor & Francis Group, 2021)
1. The representation of kingship in Castile (1252-1350): sacred monarchy, the ethos of the Reconquista, and the legitimacy troubles of an accursed lineage – 2. A kingdom comprising several realms – 3. Royal itineration and kingship in Castile (1252-1350): the kingdom's Ccapitals and the absence of a dynastic mausoleum – 4. A plural monarchy (I): queenship and royal power in Castile (1252-1350) – 5. A plural monarchy (II): defining the royal family in Castile (1252-1350) – 6. Nobles and kingship (I): the 'conflictive cooperation' between the Ricoshombres and the king in Castile (1252-1350) – 7. Nobles and kingship (II): the representation of the Castilian nobility in the Privilegios Rodados (1252-1350)
Literaturverzeichnis Seite 204-222
Keywords: Alfonso; Monarchy; Power (Social sciences)